Soil health is the basis of organic agriculture - Tomashevich Natalia; Bondarchuk Elena; Asaturova Angela (BIO Web of Conferences, 2021)
The biologization of agriculture is a topical issue both in Russia and in the world. The objective of the presented experiment was to confirm the positive effect biopreparations treatment of the fruit crops on the soil microbiota. As a result, in soil samples selected depend on the intensity of chemical fungicides application, from 1.15 x 104 to 1.23 x 104 CFU of micromycetes in one gram of absolutely dry soil were isolated. It was found that the largest amount of potentially pathogenic fungi was isolated in a soil sample cultivated using only chemical preparations - 20.5% of the total number of colonies. In the variant with the inclusion of biopreparation in the technology – from 7.2% to 11.0% of potentially pathogenic fungi of the total number of micromycetes. The most common among potentially pathogenic micromycetes were fungi of the genus Fusarium spp. Fungi of the genus Trichoderma were detected in all variants – not exceed 10% in the total number of micromycetes.